2023
DOI: 10.5114/wiitm.2023.133679
|View full text |Cite
|
Sign up to set email alerts
|

Influence of staple line reinforcement on the occurrence of bleeding complications following laparoscopic sleeve gastrectomy: a retrospective analysis.

Michal Robert Janik,
Krzysztof Jędras,
Dawid Golik
et al.

Abstract: Introduction Laparoscopic sleeve gastrectomy (LSG) has gained prominence as a therapeutic option for obesity and metabolic diseases. The choice of staple line reinforcement technique in LSG remains a subject of debate, particularly concerning postoperative bleeding complications. Aim The aim of this retrospective analysis is to assess the influence of different staple line reinforcement techniques on the occurrence of bleeding complications LSG. Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Certain studies have demonstrated superior outcomes, including reduced bleeding, when continuous suturing is applied along the stapler line. 18 Zhang et al 19 investigated the excision of lesions near the esophagogastric junction in 13 patients using their modified single-incision laparoscopic intragastric surgery with a subxiphoid incision. During a mean follow-up of 14 ± 4 months, there were no tumor recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have demonstrated superior outcomes, including reduced bleeding, when continuous suturing is applied along the stapler line. 18 Zhang et al 19 investigated the excision of lesions near the esophagogastric junction in 13 patients using their modified single-incision laparoscopic intragastric surgery with a subxiphoid incision. During a mean follow-up of 14 ± 4 months, there were no tumor recurrences.…”
Section: Discussionmentioning
confidence: 99%